2011
DOI: 10.1186/1471-2458-11-305
|View full text |Cite
|
Sign up to set email alerts
|

Parents' attitudes and behaviours towards recommended vaccinations in Sicily, Italy

Abstract: BackgroundSince a long time, Italy has maintained a dual system to administer childhood immunisations, that is a certain number of mandatory vaccinations and a number of recommended vaccinations. The study aimed to explore the issues surrounding parental acceptance or non-acceptance of the recommended vaccinations for children.MethodsParents of children aged 3-5 years of day-care centres in Sicily were asked to fill out an anonymous questionnaire. Determinants of the attitude towards recommended vaccinations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 12 publications
3
20
0
5
Order By: Relevance
“…7 Coniglio MA et al, Angelillo et al and Inamder et al also showed that most parents sought information about vaccines from the physicians. 2,3,9 In present study, television and newspaper which are an important media of information education and communication (IEC) are underutilised by the parents. It is heartening to note that doctors are responsible for informing a majority of respondents about immunization.…”
Section: Discussionmentioning
confidence: 99%
“…7 Coniglio MA et al, Angelillo et al and Inamder et al also showed that most parents sought information about vaccines from the physicians. 2,3,9 In present study, television and newspaper which are an important media of information education and communication (IEC) are underutilised by the parents. It is heartening to note that doctors are responsible for informing a majority of respondents about immunization.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study by Maria Anna Coniglio et al of the 1,500 selected parents, 81.0% participated in the study. 13 Prior to the survey, the majority of children (97.6%) received recommended vaccines. Most parents (74.4%) received information about vaccinations from Family Paediatricians, showed a good knowledge about the side effects of the vaccines (73.1%), did not worry about their potential dangerousness (53.0%) and would have accepted their children to be vaccinated even if it was not required for daycare (84.1%).…”
Section: Discussionmentioning
confidence: 99%
“…(n=41) -netiki jų veiksmingumu. Nemažai atlikta tyrimų, nagrinėjančių požiūrį į skiepijimus ir tai lemiančius veiksnius, susiję su tėvų požiūriu į vaikų skiepijimus [27][28][29][30][31]. Lietuvoje atlikto tėvų požiūrio į vaikų skiepijimus tyrimo rezultatai parodė, kad 66,7 proc.…”
Section: Rezultatų Aptarimasunclassified